Frenula in the Oral Cavity – Impact on Craniofacial Development and Respiratory Disorders. Literature Review. - Górski, Szymon; Okupniarek, Joanna; Bartosik, Michalina; Miarczyński, Jakub; Jętasiewicz, Igor; Oborski, Krzysztof; Oborski, Michał (Quality in Sport, 2026)
Frenula of the oral cavity are small anatomical structures that play a significant role in the proper functioning of the stomatognathic system. Despite their relatively simple morphology, abnormalities in the structure, length, or attachment of oral frenula may influence feeding, speech, oral hygiene, occlusion, and craniofacial development. Disorders related to labial, lingual, and buccal frenula are observed in patients of all ages and may require interdisciplinary management involving dentistry, orthodontics, speech therapy, and oral surgery. Due to the wide spectrum of clinical consequences associated with abnormal frenula, a thorough understanding of their anatomy, classification, and clinical significance is essential.